Agroturismo: innovación social para la provincia de sugamuxi (2020)
This research article is carried out within the framework of the research project “Proposal of a social innovation model as a marketing strategy for the development of Agrotourism in Boyacá: Sugamuxi Province”, endorsed by the program Young Investigators and Innovators of Colciencias 812 from 2018. In this way, the theoretical bases and the DOFA analysis carried out for the development of agrotourism in the province of Sugamuxi are presented below, as an alternative of social innovation. At first, we proceed to contextualize about the province. Subsequently, agrotourism and social innovation are addressed, as well as Colombian regulations related to the exercise of the activity, and then the DOFA analysis and its respective strategies are presented, concluding that it is a favorable place for the development of agrotourism and this can bring Great benefits to the community.